GAMBARAN PEMBERIAN OBAT PADA PENDERITA HIPERTENSI DI PUSKESMAS RAWANG - Taslim, Tuty; Betris, Yani Anggela (Jurnal Riset Kefarmasian Indonesia, 2020)
Hypertension is a disease that often causes death because many people do not realize it. People have hypertension if the blood pressure above 140/90 mmHg after regular checking. In Puskesmas Rawang, hypertension is the second-highest disease. This study aims to overview drug administration in patient's hypertension. This research is an observational descriptive study using retrospective data with the inclusion criteria. Data was taken from the recipes in April till June 2019 period. Based on the research, 82 % of women more suffer than men. While the age criteria from 41 – 61 years was 53.8%. The majority of drugs were given in Puskesmas Rawang was amlodipine with a percentage of 89%.